The Causal Association Between Obesity and Primary Open-Angle Glaucoma: A Two-Sample Mendelian Randomization Study - Lin, Yi; Zhu, Xiaomin; Luo, Wangdu; Jiang, Bingcai; Lin, Qianyi; Tang, Min; Li, Xiangji; Xie, Lin (Frontiers in Genetics, 2022)
The correlation between obesity and primary open-angle glaucoma (POAG) has not yet been fully established. The aim of this study was to investigate the causal relationship between obesity and POAG by a two-sample Mendelian randomization (MR) study. In this study, body mass index (BMI), which is an index to evaluate general obesity, and waist and hip circumference, which are indices to evaluate abdominal obesity, were selected as exposures in MR analysis. Single nucleotide polymorphisms (SNPs) were chosen as instrumental variables (IVs). Summary data from genome-wide association studies (GWASs) based on European ancestry by Locke et al., with regard to BMI, and Shungin et al., with regard to waist and hip circumference, were used. Genetic predictors of POAG were obtained from public GWAS summary data. To assess the causal effect of obesity on POAG, inverse variance weighted (IVW) was used as the primary method, and other methods, such as MR Egger, weighted median, simple mode, and weighted mode, were also used as complementary analyses. Finally, we performed Cochran’s Q statistic to assess heterogeneity, and sensitivity analysis was performed to evaluate the reliability and stability of the MR results. MR analysis showed that BMI has a positive effect on the risk of POAG, with a 1 standard deviation (SD) increase in BMI, the risk of POAG increases by approximately 90.9% [OR=1.909; 95% CI= (1.225, 2.975); P=0.0042)] (analyzed by IVW), there were not heterogeneity and pleiotropy as for the result; and waist circumference also has a positive effect on the risk of POAG [OR=2.319; 95% CI= (1.071, 5.018); P=0.033)] analyzed by weighted median. As hip circumference increases, with a 1 SD increase in hip circumference, the risk of POAG increases by approximately 119% [OR=2.199; 95% CI= (1.306, 3.703); P=0.00305)] estimated by IVW, there were not heterogeneity and pleiotropy as for the result. Our study first time confirm that obesity might increase the risk of POAG by two-sample MR analysis. These results might provide guidance on the prevention and treatment of POAG.